Legal protection of community members in the Complete Systematic Land Registration Program - I. Z. Rusmanira; . Sudarsono; M. H. Masykur (Law and Safety)
This research discusses the issue of legal protection for the community in the Complete Systematic Land Registration Program, which is motivated by the issuance of the Joint Decree of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency, Minister of Home Affairs, and Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 25/SKB/V/2017, Number 590-3167A Year 2017, Number 34 Year 2017. This decision opens up opportunities for local governments to adopt additional regulations related to the financing of PTSL, which is often a loophole for illegal extortion. This study raises the question of how legal protection of the community in the process of implementing PTSL. The research method used is a regulatory and legal one with the use of the statutory and conceptual approaches. The results of the analysis show that the Ratio Legis of the Joint Decree is philosophically a form of application of Pancasila and the 1945 Constitution, especially Article 33 paragraph (3) and Article 28D paragraph (1), which emphasize protection and legal certainty for the community. Sociologically, the program is designed to accelerate land legalization by considering the geographical conditions and social diversity of Indonesian society. However, legal protection in PTSL is mostly repressive, while preventive protection is inadequate. Regulatory adjustments are needed, including the determination of fair fees based on geographical difficulties and land contours, as well as continuous evaluation and supervision to prevent corrupt acts and illegal levies in this program. This is important to ensure transparency, accountability and a focus on social justice for all segments of society.